Total Synthesis of Putative 11-epi-Lyngbouilloside Aglycon - Kolleth, Amandine; Gebauer, Julian; ElMarrouni, Abdelatif; Lebeuf, Raphael; Prévost, Céline; Brohan, Eric; Arseniyadis, Stellios; Cossy, Janine (Frontiers in Chemistry, 2016)
We report here the total synthesis of 11-epi-lyngbouilloside aglycon. Our strategy features a Boeckman-type esterification followed by a RCM to form the 14-membered ring macrolactone and a late-stage side chain introduction via a Wittig olefination. Overall, the final product was obtained in 20 steps and 2% overall yield starting from commercially available 3-methyl-but-3-enol. Most importantly, the strategy employed is versatile enough to eventually allow us to complete the synthesis of the natural product and irrevocably confirm its structure.